A high gain 10 watts wideband distributed power amplifier for two way radio system - Sangaran, Pragash; Kumar, Narendra; Rajendran, Jagadheswaran; Grebennikov, Andrei (Emerald, 2018)
Purpose – This paper aims to propose a practical design methodology of high-power wideband power amplifier. Design/methodology/approach – The distributed power amplification method is used for a Gallium Nitride device to achieve wideband operation. To achieve the high power without trading-off the bandwidth and gain, a methodology to extract the package-loading effect is proposed and verified. Findings – A maximum output power of 10 W is achieved from 100 MHz to 2 GHz with a wideband power gain of 32 dB in measurement. This performance is achieved through a single section matching network. Research limitations/implications – Measurement accuracy is dependable to the thermal behaviour of the high-power device. Practical implications – The proposed technique is an excellent solution to be used in the two way radio power amplifier that minimizes the fundamental trade-off issue between power, gain, bandwidth and efficiency. Originality/value – In this work, a practical distributed power amplifier (DPA) design methodology is proposed that reduces the development cycle time for industrial engineers working on high-power circuit design application.